Hypocoagulable Tendency on Thromboelastometry Associated With Severity and Anticoagulation Timing in Pediatric Septic Shock: A Prospective Observational Study - Tuan, Ta Anh; Ha, Nguyen Thi Thu; Xoay, Tran Dang; My, Tran Thi Kieu; Nghiem, Luong Thi; Dien, Tran Minh (Frontiers in Pediatrics, 2021)
Objective: To identify whether coagulation profiles using thromboelastometry are associated with outcomes in pediatric septic shock. The primary outcomes were the development of disseminated intravascular coagulation (DIC) and the severity of the pediatric intensive care unit (PICU) existing scoring systems, while the secondary outcome was hospital mortality. This study aimed to contribute to current findings of the limitations of conventional tests in determining the optimal timing of anticoagulation in sepsis. Design: A prospective, observational study conducted between August 2019 and August 2020. Setting: PICU at a pediatric tertiary hospital in Hanoi, Vietnam. Patients: Fifty-five pediatric patients who met the septic shock criteria were enrolled. Interventions: None. Measurements and Main Results: Fifty-five patients with septic shock were recruited. At the time of diagnosis, thromboelastometry revealed normocoagulability, hypercoagulability, and hypocoagulability in 29%, 29%, and 42% of the patients, respectively (p >0.05); however, most patients in the overt DIC and non-survival groups progressed to hypocoagulability (82% and 64%, respectively). The overt DIC, PELOD-2 >8, PRISM-III >11, and non-survival group had a significant hypocoagulable tendency according to thromboelastometry parameters [prolonged clotting time (CT) and clot formation time (CFT); and reduced α-angle (α), maximum clot firmness (MCF), thrombodynamic potential index (TPI)] compared to the non-overt DIC, PELOD-2 ≤8, PRISM-III score ≤11 and survival group (p <0.05). Conventional parameters between the normocoagulable and hypercoagulable groups were not different (p >0.05). Hypocoagulability was characterized by lower platelet count and fibrinogen level, higher prolonged prothrombin time (PT), international normalized ratio (INR), and activated partial thromboplastin time (APTT), and higher D-dimer level than in hypercoagulability (p <0.05). Hypocoagulable tendency on thromboelastometry had a higher hazard at a PT >16.1 s (area under the curve [AUC] = 0.747, odds ratio [OR] = 10.5, p = 0.002), INR >1.4 (AUC = 0.754, OR = 6.9, p = 0.001), fibrinogen <3.3 g/L (AUC = 0.728, OR = 9.9, p = 0.004), and D-dimer >3863 ng/mL (AUC = 0.728, OR = 6.7, p = 0.004). Conclusions: Hypocoagulable tendency using thromboelastometry is associated with the severity of septic shock. Conventional coagulation tests may fail to detect hypercoagulability, which is crucial in determining anticoagulation timing.